2016
DOI: 10.1152/ajplung.00156.2014
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial-cadherin downregulation as a feature of endothelial transdifferentiation in monocrotaline-induced pulmonary hypertension

Abstract: Increased pulmonary vascular resistance in pulmonary hypertension (PH) is caused by vasoconstriction and obstruction of small pulmonary arteries by proliferating vascular cells. In analogy to cancer, subsets of proliferating cells may be derived from endothelial cells transitioning into a mesenchymal phenotype. To understand phenotypic shifts transpiring within endothelial cells in PH, we injected rats with alkaloid monocrotaline to induce PH and measured lung tissue levels of endothelial-specific protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Recent studies indicate that EndMT is a major cause of pulmonary artery remodeling in MCT-induced PAH in rats 16 . Using double immunofluorescence staining and semi-quantitative analysis, Nikitopoulou et al found that endothelial markers are downregulated and mesenchymal markers are upregulated in MCT-induced pulmonary hypertension 52 . Ghosh et al found that treatment with SB431542, the TGFβ receptor inhibitor, could completely block TGFβ-induced EndMT 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that EndMT is a major cause of pulmonary artery remodeling in MCT-induced PAH in rats 16 . Using double immunofluorescence staining and semi-quantitative analysis, Nikitopoulou et al found that endothelial markers are downregulated and mesenchymal markers are upregulated in MCT-induced pulmonary hypertension 52 . Ghosh et al found that treatment with SB431542, the TGFβ receptor inhibitor, could completely block TGFβ-induced EndMT 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, transdifferentiation of mature vascular ECs has been detected in pulmonary hypertension, which plays an important role in pulmonary arterial remodeling ( 73 ). This likely happens due to downregulation of EC-cadherin ( 74 ) or regulation by myocardin in hypoxia-induced pulmonary vascular remodeling ( 75 ). However, the causal role of EC-derived VSMC in atherogenesis, if any, remains poorly understood ( 5 ).…”
Section: Ec-vsmc Interaction Via Other Factors Affmentioning
confidence: 99%
“…Besides, accumulation of inflammatory cells around pulmonary arteries, including macrophages and mast cells, is another obvious profile of pulmonary vascular remodeling (PRV) [5]. Recently, endothelial-mesenchymal transition (EndMT) has been noted in the pulmonary vascular intima both in patients with PH [6, 7] and in animal model of PH [6, 8]. EndMT results in endothelial dysfunction and pro-inflammatory response [9].…”
Section: Introductionmentioning
confidence: 99%